2009
DOI: 10.1007/978-3-642-04271-3_44
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Chest Surface Motion to Motion of the Liver Using ε-SVR – A Porcine Study

Abstract: Abstract. In robotic radiosurgery, the compensation of motion of internal organs is vital. This is currently done in two phases: an external surrogate signal (usually active optical markers placed on the patient's chest) is recorded and subsequently correlated to an internal motion signal obtained using stereoscopic X-ray imaging. This internal signal is sampled very infrequently to minimise the patient's exposure to radiation. We have investigated the correlation of the external signal to the motion of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 8 publications
3
27
0
Order By: Relevance
“…Furthermore, higher order models did not improve the overall fit of the data. The results show that using only one marker would result in a lower accuracy than using two markers, confirming the results of Ernst et al Moreover, the location of the marker affects the estimation accuracy: the closer the marker was to the umbilicus the higher the estimation accuracy. The results also illustrated the accuracy of the estimated SI liver motion; the MAE ranged between 0.8 mm and 1.9 mm for the 3 regression models.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, higher order models did not improve the overall fit of the data. The results show that using only one marker would result in a lower accuracy than using two markers, confirming the results of Ernst et al Moreover, the location of the marker affects the estimation accuracy: the closer the marker was to the umbilicus the higher the estimation accuracy. The results also illustrated the accuracy of the estimated SI liver motion; the MAE ranged between 0.8 mm and 1.9 mm for the 3 regression models.…”
Section: Discussionsupporting
confidence: 87%
“…However, since shrinkage methods might outperform MVR in the case of high dimensional data, using more than two markers will increase the system dimensionality and thus might improve the estimation accuracy in Ridge and Lasso. In fact, multiple markers have been used in previous studies, which indicated that their use will increase the system dimensionality and might capture more complex breathing patterns …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also possible to apply correspondence models between external markers (chest and abdominal area pointers) and internal fiducials to indirectly estimate tumor position in optical images [3, 4]. Yet, the correlation between external markers and tumor position may be violated easily as a result of complex respiratory biomechanics [5].…”
Section: Introductionmentioning
confidence: 99%